2001
DOI: 10.2176/nmc.41.29
|View full text |Cite
|
Sign up to set email alerts
|

Kissing Mirror Image Anterior Communicating Artery Aneurysms. Case Report.

Abstract: A 45-year-old male presented with an extremely rare case of symmetrical kissing aneurysms located at the both ends of the anterior communicating artery. Angiography and three-dimensional computed tomography (3D-CT) angiography clearly showed the relationship of the kissing aneurysms. The aneurysms were clipped through the right pterional approach. Temporary clipping of the anterior cerebral arteries for 5 minutes was required to gain enough operative space. The patient was discharged without neurological defic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 8 publications
0
29
0
Order By: Relevance
“…Subsequently, puncture examination was performed to check whether aneurysms were completely clipped. An attempt was made not to dissect the adhesion walls between aneurysms prior to clipping to prevent rupture and hemorrhage (19,20). The advantage of this method is that once aneurysm rupture and hemorrhage occur in the course of exploration for aneurysms, they may be instantly and temporarily blocked.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, puncture examination was performed to check whether aneurysms were completely clipped. An attempt was made not to dissect the adhesion walls between aneurysms prior to clipping to prevent rupture and hemorrhage (19,20). The advantage of this method is that once aneurysm rupture and hemorrhage occur in the course of exploration for aneurysms, they may be instantly and temporarily blocked.…”
Section: Discussionmentioning
confidence: 99%
“…Eight studies have described kissing aneurysms. 1,[5][6][7][8][11][12][13] The ipsilateral internal carotid artery is the most common origin of kissing aneurysms. The detailed clinical features of kissing aneurysms have recently been reviewed elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed clinical features of kissing aneurysms have recently been reviewed elsewhere. 11) A review of large series of ophthalmic segment aneurysms revealed several characteristics. 2,3,13) These aneurysms occur predominantly in women, and are frequently associated with aneurysms at other sites, including symmetrical carotidophthalmic artery aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…Kissing aneurysms can be defined as two anatomically adjacent aneurysms of different origin arteries, with the walls partially, pressed together 1,2,6,8,9,11) . In the circle of Willis, these aneurysms are quite rare and 0.2% incidence was reported by Yasargil 12) .…”
Section: Introductionmentioning
confidence: 99%